Cover Image, Volume 37, Issue 8. (August 2017) - Svirsky, Ran; Reches, Adi; Brabbing‐Goldstein, Dana; Bar‐Shira, Anat; Yaron, Yuval
Abstract : Transabdominal sonogram performed at 15 weeks of gestation. The white arrows demonstrate an aberrant right subclavian artery behind the fetal trachea. From Svirsky et al ., Prenatal Diagnosis37 : 808‐811, DOI:10.1002/pd.5092 .